Peran Motivasi Internal dalam Pengobatan Penyakit Fibromyalgia - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Ika Sandra Dewi; Milna Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This research examines the role of internal motivation in the success of fibromyalgia treatment through a systematic review and meta-analysis. Out of 1,247 identified articles, 27 studies met the inclusion criteria. The meta-analysis results indicate a significant positive correlation between internal motivation and medication adherence (r = 0.42, p < 0.001), as well as quality of life (r = 0.38, p < 0.001) among fibromyalgia patients. Additionally, a significant negative relationship was found between internal motivation and pain intensity (r = -0.31, p < 0.001). Moderator analysis revealed that the effect of internal motivation is stronger in behavioral interventions compared to pharmacological treatments (Q = 8.7, p = 0.003). Furthermore, meta-regression results indicated that disease duration significantly moderates the relationship between internal motivation and fibromyalgia treatment (? = -0.02, p = 0.03), with internal motivation having a more substantial effect in patients with a longer duration of illness. Additionally, the average age of fibromyalgia patients was found to moderate the relationship between internal motivation and patient quality of life (? = 0.01, p = 0.02). Among six clinical trials evaluating interventions to enhance internal motivation, the meta-analysis showed a significant effectiveness (d = 0.56, 95% CI: 0.38 to 0.74, p < 0.001). Consequently, these findings extend previous research by Ng et al. (2015) on the role of internal motivation in chronic conditions, demonstrating its strong relevance in the context of fibromyalgia. This study also differs from Karlsson et al. (2019), which did not find a significant correlation. The results reveal a consistent relationship between internal motivation and fibromyalgia treatment outcomes. Lastly, the novelty of this study lies in identifying specific moderating factors and providing a comprehensive evaluation of motivation-based interventions in the context of fibromyalgia.